Stability and expansivity of tent map - Carrasco-Olivera D. (2021)
We discuss the stability and the expansivity of the tent map f: [0, 1] ? [0, 1] defined by f(x) = 2 min{x, 1 ? x} for 0 ? x ? 1. Indeed, we show that f is neither topologically stable nor orbit shift topologically stable nor countably-expansive but is cw-topologically stable, orbit shift cw-expansive, and orbit shift ?-persistent. © 2020 American Mathematical Society